2018
DOI: 10.1111/eip.12560
|View full text |Cite
|
Sign up to set email alerts
|

Exploring functional impairment in young people at ultra‐high risk for psychosis: A qualitative study

Abstract: We propose a model that attempts to explain how these variables interact to drive and sustain functional impairment in the UHR population. This will assist in the development of clinical interventions aimed at promoting functional recovery among UHR individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
9
0
1
Order By: Relevance
“…Moreover, it is important to consider that childhood adversity and trauma may have different detrimental effects on individuals with impacts on brain development, cognition, interpersonal behavior and clinical symptoms. Additional unmeasured variables, such as genetic risk and neighborhood environmental factors, may also account for aspects of observed associations [ 65 ]. Furthermore, it should be noted that interestingly the TADS sum score was higher in the group included into the analyses than in the excluded patients from the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to consider that childhood adversity and trauma may have different detrimental effects on individuals with impacts on brain development, cognition, interpersonal behavior and clinical symptoms. Additional unmeasured variables, such as genetic risk and neighborhood environmental factors, may also account for aspects of observed associations [ 65 ]. Furthermore, it should be noted that interestingly the TADS sum score was higher in the group included into the analyses than in the excluded patients from the sample.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important because there is evidence that a significant percentage of ARMS individuals continue to function poorly in the long term, regardless of symptomatic remission ( Addington et al, 2011 ). In a recent qualitative study, Cotter et al (2019) found that ARMS individuals attributed their impairment in social and occupational functioning to a combination of clinical, cognitive, and psychological factors, such as self-stigmatizing attitudes and dysfunctional metacognitive beliefs. It is important to note that the FHR group showed a good level of functioning, which confirms that a family history of psychosis is a significant risk factor but not an impediment for certain people to be able to perform adequately.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study group decided to primarily focus on quality of life, self-efficacy, and functioning. These areas have been shown to be most impacted in adolescents and often prompt them to seek help (18, 30, 44, 86, 87). In contrast, at-risk symptoms are not necessarily the cause of the highest psychological strain and burden for the patient.…”
Section: Discussionmentioning
confidence: 99%